Az 1–11 évfolyamot átfogó induktív gondolkodás kompetenciaskála készítése a valószínűségi tesztelmélet alkalmazásával - Molnár, Gyöngyvér; Csapó, Benő (Magyar Pedagógia, 2011)
Measuring general cognitive abilities bears special relevance for education. Inductive reasoning, which has often been related to general intelligence, is such an ability. Most previous measurements have focused on single measurement points; however, abilities can also be studied from a developmental perspective. The paper outlines the developmental tendencies and individual differences in inductive reasoning for a broad age range (ages 6 to 17). Common anchor items allowed the transfer of all results to the same scales. An IRT model was used to scale the data and to establish a developmentally valid scale. Large differences were found at individual and cohort levels as well, while speed of development was relatively slow, at about one-quarter standard deviation per year. The fitted logistic curves indicated a rapid change around year 7; then speed of development slowed. The individual differences in the same year grew when older age groups were considered. At the end of compulsory schooling, the difference was more than treble what was computed at school entrance. Findings support the views that there exist differences equivalent to several years of development within the same age groups in the area of general cognitive ability.